Exploring genetic variation and stripe rust resistance in ICARDA's spring bread wheat (Triticum aestivum L.) using GWAS in West Asia and North Africa (WANA) region - Youssef, Alaa; El-soda, Mohamed; H. Osman, Neama; Shahin, Atef; Zakaria, EL Gataa; Hamwieh, Aladdin; Tawkaz, Sawsan; Nazari, Kumarse; Al-Shamaa, Khaled; Tadesse, Wuletaw (Elsevier, 2025)
Stripe rust, caused by Puccinia striiformis f. sp. tritici, poses a major threat to global wheat (Triticum aestivum) production. This study assessed stripe rust resistance in 154 spring bread wheat genotypes from ICARDA, tested across four locations: Izmir (Turkey), Merchouch (Morocco), Sakha, and Sids (Egypt). Disease severity was evaluated at the adult plant stage under natural infection using the coefficient of infection (CI). Genotyping was performed using 17,692 high-quality SNP markers, and genome-wide association studies (GWAS) identified significant marker-trait associations (MTAs) for resistance. The mixed linear model (MLM), accounting for population structure and relatedness, detected significant differences in genotype resistance across locations. Twenty elite genotypes, including G101, G117, and G125, exhibited high resistance across all sites. A total of 136 significant MTAs and 17 candidate genes were identified, with −log10(p) > 3.0, primarily on chromosomes 2A, 3B, 4A, 5B, and 7A. Several MTAs aligned with known resistance genes, such as Yr18 and Yr57, while others suggested novel loci. Key markers, including ‘AX-109902001’ (6A), ‘AX-94992026’ (7B), ‘IAAV1650’ (5A), and ‘Excalibur_c37115_306’ (3B), were significantly associated with resistance across locations. These findings enhance the understanding of the genetic architecture of stripe rust resistance and provide MTAs suitable for marker-assisted selection to pyramid resistance genes. The identified resistant genotypes hold potential for direct release or use as breeding parents in the WANA region, pending further adaptation trials assessing yield stability and agronomic performance.